2019
DOI: 10.1161/circgen.119.002471
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chromosome 9p21 With Subsequent Coronary Heart Disease Events

Abstract: Background: Genetic variation at chromosome 9p21 is a recognized risk factor for coronary heart disease (CHD). However, its effect on disease progression and subsequent events is unclear, raising questions about its value for stratification of residual risk. Methods: A variant at chromosome 9p21 (rs1333049) was tested for association with subsequent events during follow-up in 103 357 Europeans with established CHD at baseline from the GENIUS-CHD (Geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…Our study revealed an association of the G allele of rs1333049 with TC and LDL-C levels among males. These data contradict some other studies [10,11,33], for example, Ellis et al have demonstrated a correlation of the C/C genotype with higher TG and TC levels in blood [26]. The study by Ellis et al was performed on patients with ischemic heart disease (New Zealand), whereas our study deals with the general population.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Our study revealed an association of the G allele of rs1333049 with TC and LDL-C levels among males. These data contradict some other studies [10,11,33], for example, Ellis et al have demonstrated a correlation of the C/C genotype with higher TG and TC levels in blood [26]. The study by Ellis et al was performed on patients with ischemic heart disease (New Zealand), whereas our study deals with the general population.…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast to studies comparing individuals with CHD to disease-free controls, they found no clear association between genetic variation in chromosomal region 9p21 and the risk of subsequent acute CHD events when all individuals had CHD at baseline. Nonetheless, they uncovered an association with subsequent revascularization, which may support the postulated mechanism of promotion of atheroma development by chromosomal region 9p21 [10]. Data from Russian patients have confirmed the correlation of rs1333049 with myocardial infarction but not with type 2 diabetes; these studies had some limitations because they involved only small groups [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by the GENIUS-CHD (Genetics of Subsequent Coronary Heart Disease) consortium, albeit a survivors’ cohort, reveals that this locus is not associated with recurrent events in patients with established CAD. It does, however, confer an increased risk for revascularization, 12 consistent with a primary role in atherosclerosis.…”
Section: Genetics Of Coronary Artery Diseasementioning
confidence: 83%
“…Genome-wide association studies (GWAS) attempt to discover associations between genetic variants and a particular phenotype (an outcome)[1]. Due to an increased interest in GWAS of subjects who develop disease (see for example the ongoing Genetics of Subsequent Coronary Heart Disease consortium[2–4]) genetic analyses will more frequently be conducted using information about subjects who have received pharmacological (or other kinds of) treatments.…”
Section: Introductionmentioning
confidence: 99%